Instructional Model Development for Painting - Tri Aru Wiratno; Diana Nomida Musnir; Atwi Suparman (JETL (Journal of Education, Teaching and Learning), 2020)
Students can paint by developing ideas and ideas through deductive and constructive learning. Painting subject is a subject that is synonymous with learning painting skills. The technical mastery of painting is based on one's talent in the learning process of painting. Painting well is a satisfaction for a painter. Students are required to have a soul of creativity and know themselves as whole individuals in their lives. To grow in a new awareness about what are the ideas of his work, we need a learning model. With deductive and constructivist learning models that provide space for everyone to grow and develop themselves in learning painting. Developing a learning model of painting to be better and more effective and structured in painting without reducing the power of expression in making paintings. The development model in this study uses the Dick and Carey Model and the research method uses the Borg and Gall model. The results of this study are in the form of a development model of learning to work in painting that can increase interest and rank and insight in the field of painting.